Power Despite Precarity: Strategies for the Contingent Faculty Movement in Higher Education - Batson, Michael (Radical Teacher, 2022)
Review of Power Despite Precarity: Strategies for the Contingent Faculty Movement in Higher Education, by Joe Berry and Helena Worthen London: Pluto Press, 2021.